Deconstructing the Problematic Roles of Pakistani Media During the Covid-19 Pandemic (Law, State and Telecommunications Review, 2024)
[Purpose] This study assesses the duties of the mass media operating in Pakistan, the state of its affairs, and the domestic roles it can play in benefiting communities in distress, especially during the pandemic caused by the coronavirus. Media workers use “emergency” as a generic term to describe all sorts of crises, including an outbreak. Although it fulfills the essential criteria on which disseminators can devise a crisis management plan, it does not address the core issue: how a health emergency differs from other disasters. In the sociocultural context, the role of media personnel in Pakistan becomes more problematic due to several shortcomings. As public and community health is not up in mainstream media’s agenda and they focus more on politico-social issues, the media workers’ job of collecting data, writing facts, and sharing information becomes more challenging.[Methodology/Approach/Design] This study entails a mixed method with a descriptive approach based on empirical data to analyze the media’s role in Pakistan and forecast its duties during the COVID-19 epidemic. For COVID-19 integrated statistics, it drew upon the numeric data provided by domestic and international health organizations.[Findings] For a qualitative assessment, the authors organized a survey reflecting the responsibilities of media and problematics of Pakistani media amid emergencies using a 5-point Likert Scale. The survey was conducted through random phone calls, following the government’s directions regarding standard operating procedures (SoPs) amid the pandemic.